"You're Either One of Us or You're Not": Racial Hierarchy and Non-Black Members of Black Greek-Letter Organizations. Issue 4 (October 2017) - Laybourn, Wendy M.; Goss, Devon R.; Hughey, Matthew W.
Colleges and universities across the United States tout the importance of racial diversity, yet highly public racialized incidents persist. Historically, Black Greek-letter organizations (BGLOs) were created in the early twentieth century in response to the racism Black students experienced on college campuses. While previous literature provides evidence for the positive effects of BGLOs for Black members, less is known about if and how these effects of BGLO membership extend to non-Black members. Drawing on 34 in-depth interviews with non-Black members of BGLOs, we seek answers to three yet unasked questions: First, why do non-Blacks come to identify with BGLOs? Second, what are the responses and reactions to this identification process and experience? And finally, how does this identification relate to larger shifts in the United States's racial hierarchy? We find that campus racial climate acts as a catalyst for BGLO membership and that BGLOs continue to serve their purpose as a necessary counter-space but that also, non-Blacks come to identify with these organizations in order to develop meaningful interracial solidarity and oppose their hostile campus climates.